2022
DOI: 10.1186/s12985-022-01740-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold case: The disappearance of Egypt bee virus, a fourth distinct master strain of deformed wing virus linked to honeybee mortality in 1970’s Egypt

Abstract: In 1977, a sample of diseased adult honeybees (Apis mellifera) from Egypt was found to contain large amounts of a previously unknown virus, Egypt bee virus, which was subsequently shown to be serologically related to deformed wing virus (DWV). By sequencing the original isolate, we demonstrate that Egypt bee virus is in fact a fourth unique, major variant of DWV (DWV-D): more closely related to DWV-C than to either DWV-A or DWV-B. DWV-A and DWV-B are the most common DWV variants worldwide due to their close re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
1
20
1
Order By: Relevance
“…A third variant has since been described, DWV-C ( Mordecai et al, 2016 ), though unlike DWV-A and DWV-B it is rarely reported. A fourth variant, DWV-D, has recently been recovered from Egyptian honey bees collected in the 1970s but has never been reported since ( de Miranda et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A third variant has since been described, DWV-C ( Mordecai et al, 2016 ), though unlike DWV-A and DWV-B it is rarely reported. A fourth variant, DWV-D, has recently been recovered from Egyptian honey bees collected in the 1970s but has never been reported since ( de Miranda et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, a previous study in the UK found 40% higher DWV titers when screening with a universal DWV-complex assay than by pooling the results of screening with specific DWV-A and DWV-B assays [68]. Possible explanations can be the presence of different genotypes, DWV-C or DWV-D, neither of which has so far been detected in Belgium [27,28], or mutations in the primer region that hamper correct primer hybridization [69]. A study on the genetic diversity within a DWV population in a colony showed that 82% of the genome had >1 sequence variant present in the frequency of >1%, and 39% of the genome had >1 sequence variant present in a frequency of >10% [8].…”
Section: Discussionmentioning
confidence: 87%
“…Of the 72 virus species that have been identified in honey bees [22], the most commonly occuring belong to Iflaviridae and Dicistroviridae [23,24], particularly sacbrood virus (SBV), black queen cell virus (BQCV), acute bee paralysis virus (ABPV) and deformed wing virus (DWV), with both ABPV and DWV consisting of a complex of closely related, co-circulating master variants capable of forming viable recombinants [22,25,26]. The DWV virus complex is best described as a group of functionally and genetically compatible minor and major variants and their recombinants based on four master strains [27], of which DWV-A and DWV-B are currently the most common [28][29][30][31][32][33]. Dynamics in the presence and abundance of honey bee viruses show strong seasonal and geographic variation [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Here, only a very small inoculum is needed to induce infection through injections (as performed by V. destructor parasitizing honeybees) [ 71 ], which is in the same order of magnitude as for SARS-CoV-2. Recently, a fourth major variant has been identified (DWV-D) via a sequencing analysis of old honeybee samples [ 72 ]. However, a large effort to detect the current presence of this variant, by screening RNA libraries from different bee hosts and varroa mites, across the world, did not result in the detection of the DWV-D variant.…”
Section: Viruses and Their Variantsmentioning
confidence: 99%
“…However, a large effort to detect the current presence of this variant, by screening RNA libraries from different bee hosts and varroa mites, across the world, did not result in the detection of the DWV-D variant. Either this variant has gone extinct, is replaced by or pushed back by other variants, or is only present in a very restricted geographical area [ 72 ]. The change in dominant variants of DWV is also documented in the UK and USA, where over the last 5 to 10 years the previously dominant DWV-A variant is being replaced by the DWV-B variant [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Viruses and Their Variantsmentioning
confidence: 99%